Solid-Supported Synthesis of Flexible Dimeric Pyridinium Salts and Their Catalytic Activities - Manikandan, Chitrarasu; Ganesan, Kilivelu (Synlett, 2016)
The synthesis of flexible dimeric pyridinium ionic liquids by both conventional and solid-supported approaches are described. We have optimized the Biginelli reaction with various concentrations of our synthesized ionic liquids with various counter ions. Among these, bromide-containing ionic liquids showed best catalytic activity.
Keywords: ionic liquid; o-alkylation; solid supported; Biginelli reaction